An experimental conflict of interest between parasites reveals the mechanism of host manipulation - Hafer, Nina (Behav Ecol, 2016)
Parasites can increase their host’s predation susceptibility. It is a long-standing puzzle, whether this is caused by host manipulation, an evolved strategy of the parasite, or by side effects due to, for example, the parasite consuming energy from its host thereby changing the host’s trade-off between avoiding predation and foraging toward foraging. Here, we use sequential infection of three-spined sticklebacks with the cestode Schistocephalus solidus so that parasites have a conflict of interest over the direction of host manipulation. With true manipulation, the not yet infective parasite should reduce rather than enhance risk taking because predation would be fatal for its fitness; if host behavior is changed by a side effect, the 2 parasites would add their increase of predation risk because both drain energy. Our results support the latter hypothesis. In an additional experiment, we tested both infected and uninfected fish either starved or satiated. True host manipulation should act independently of the fish’s hunger status and continue when energy drain is balanced through satiation. Starvation and satiation affect the risk averseness of infected sticklebacks similarly to that of uninfected starved and satiated ones. Increased energy drain rather than active host manipulation dominates behavioral changes of S. solidus-infected sticklebacks.